Estudo da aplicação de brometo de índio(I) em reações para formação de ligações carbono-carbono - Chagas, Rafael Pavão das (2011)
This PhD thesis describes our results on the application of indium(I) bromide in carbon-carbon bond forming reactions. Indium enolates, generated in situ from the reaction between indium(I) bromide and α,α-dichloroketones, react with carbonyl compounds and electron-deficient alkenes. Reactions of indium enolate with α,α-dichloroketones, in presence of extra InBr, leads to the formation of 1,4-diketones. The coupling with aldehydes leads alternatively, according as the stoichiometry, to the diastereoselective synthesis of (syn+anti)-2-chloro-3-hydroxy-propan-1-ones (which can be converted to the respective trans-epoxyketones), (E)-α,β-unsaturated ketones and cyclopropanes, upon a sequenced reaction mechanism. We also have developed a methodology for the preparation of cyclopropanes through the reaction of the indium enolate and other organoindium(III) compounds, derived from the reactions between InBr and α,α-dihalo carbonyl compounds and halo-acetonitriles, with electron-deficient alkenes.